Formulation, Optimization, and Standardization of Polyherbal Facial Scrub Containing Coffee Arabica, Walnut Shell Along with Turmeric and Neem: Formulation and characterization of polyherbal facial scrub - Kaushik, Aayush; Pal, Chandan; Tripathi, Saurabh; Singh, Mahendra; Tuteja, Minkal (Iranian Journal of Pharmaceutical Sciences, 2024)
The present study was designed to prepare a polyherbal facial scrub containing coffee arabica, walnut shell, turmeric, neem, honey, and a mixture of pulses. Further, the prepared scrub was optimized using two factors and three central composite experimental design levels. The phytochemical screening and standardization of scrub were accomplished. The extracts were prepared, standardized, and evaluated using smear type, homogeneity, pH, spreadability, acid value, and stability tests. The influence of the concentration of honey (%) and paraffin wax (%) on pH and spreadability was premeditated using response surface methodology. Further, the optimized batch of polyherbal scrub was compared with the marketed formulation of Everyuth scrub containing walnut as the main ingredient, which was almost equivalent in pH, spreadability, acid value, and homogeneity. The study revealed that enhancing the concentration of paraffin wax in polyherbal scrub increases the pH and spreadability. The optimal calculated parameters were the concentration of honey 2.3 (%) and the concentration of paraffin wax 2.1 (%). The optimized batch of polyherbal scrub had a pH of 6.8 and spreadability of 7.3. Thus, the prepared formulations can be effectively used for facial care.